2000
DOI: 10.1038/sj.cgt.7700124
|View full text |Cite
|
Sign up to set email alerts
|

SEREX analysis for tumor antigen identification in a mouse model of adenocarcinoma

Abstract: Evaluation of immunotherapy strategies in mouse models of carcinoma is hampered by the limited number of known murine tumor antigens (Ags). Although tumor Ags can be identified based on cytotoxic T-cell activation, this approach is not readily accomplished for many tumor types. We applied an alternative strategy based on a humoral immune response, SEREX, to the identification of tumor Ags in the murine colon adenocarcinoma cell line MC38. Immunization of syngeneic C57BL/6 mice with MC38 cells by three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Following the initial development of SEREX by Sahin et al [9] the serological approach for the identification of human tumor antigens has been applied to several tumor types [11][12][13][14]20,23,27,[30][31][32][33][34][35][36][37][38][39][40] resulting in the identification of more than 2,500 antigens, one-third of which are novel. A proportion of tumor antigens, identified via this method and other approaches, form a unique class of differentiation antigens with expression confined to tumor tissue and normal testis, placenta and embryonic tissue; this led to their designation as cancer testis antigens [18,25,26,[41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Following the initial development of SEREX by Sahin et al [9] the serological approach for the identification of human tumor antigens has been applied to several tumor types [11][12][13][14]20,23,27,[30][31][32][33][34][35][36][37][38][39][40] resulting in the identification of more than 2,500 antigens, one-third of which are novel. A proportion of tumor antigens, identified via this method and other approaches, form a unique class of differentiation antigens with expression confined to tumor tissue and normal testis, placenta and embryonic tissue; this led to their designation as cancer testis antigens [18,25,26,[41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Bearing in mind these assumptions, it is important to focus the search for GBM-related antigens on those antigens that have induced an antibody response in the patient. We used a combined immunological and molecular approach known as the SEREX method to detect GBM-related antigens (Sahin et al, 1995;Tureci et al, 1997;Hampton et al, 2000). PHF3 was identi®ed from a GBM cDNA library using autologous patient serum in the immunological screening.…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies linking different levels of expression of ATRX as drivers of specific phenotypes that give rise to disease and cancer [13,18,19]. In the present study, we searched human somatic cancer databases and found that the ATRX gene is overexpressed in a wide variety of human cancers.…”
Section: Introductionmentioning
confidence: 81%